Genetic and Epigenetic Biomarkers For Diagnosis, Prognosis and Treatment Of Metabolic Syndrome - Giglio, Rosaria V; Stoian, Anca P; Patti, Angelo M; Rizvi, Ali A; Sukhorukov, Vasily; Ciaccio, Marcello; Orekhov, Alexander; Rizzo, Manfredi (Current pharmaceutical design, 2021)
Metabolic syndrome is a clinical condition that deserves special attention because it puts the individual at high cardiovascular risk, especially heart attack and stroke. Considering the precision medicine, it would be advisable to valuate the individual cardio-metabolic risk by estimating the coesistence of risk factors (abdominal obesity, low level of High- Density Lipoprotein Cholesterol, High Triglycerides, and small dense Low-Density Lipoproteins sub-classes, hypertension, and elevated fasting glycemia), which could engrave on metabolism increasing cardiovascular mortality. To identify genetic and epigenetic biomarkers may assist in the possibility of helping follow-up strategies and other measures of prevention, and in metabolic risk. We searched for studies which valued the combination between epigenetic biomarkers and all factors of cardio-metabolic risk. Numerous researches have investigated the molecular start of metabolic alterations, focusing on the epigenetic mark, as methylation of DNA, histone modifications and non.coding RNAs. It has been found that DNA methylation is the most searched epigenetic sign in the human genome concerning the control of gene expression. For the screening, diagnosis, and prognosis of metabolic syndrome and the prescription of personalized medicine, the DNA methylation biomarkers specify for subjects have been recognized as an ensuring tool. While these results are promising, further investigations are needed to unravel the complicated synergic association of the genome, epigenome and the situations related to metabolic pathology.